SIGnature Libraries: A roadmap for the formation of special interest group libraries - Young‐Min Kim; Eric M. Chin; Michael Fahey; Rose Gelineau‐Morel; Kate Himmelmann; Jennifer O'Malley; Maryam Oskoui; Bruce Shapiro; Michael Shevell; Jenny L. Wilson; Max Wiznitzer; the Child Neurology Society Cerebral Palsy Special Interest Group Consortium; et al. (Annals of the Child Neurology Society)
Abstract Objective “SIGnature Libraries” channel the dynamism of academic society‐based special interest groups (SIG) to systematically identify and provide user‐oriented access to essential literature for a subspecialty field in a manner that keeps pace with the field's continuing evolution. The libraries include literature beyond clinical trial data to encompass historical context, diagnostic conceptualization, and community organization materials to foster a holistic understanding of how neurologic conditions affect individuals, their community, and their lived experience. Methods Utilizing a modified‐Delphi approach, Child Neurology Society's Cerebral Palsy (CP) SIG (n = 75) administered two rounds of literature submissions and ratings. A final review by an 11‐member international advisory group determined threshold ratings for resource inclusion and the library's final structure. Results Seventy‐nine articles were submitted for the first Delphi round and 22 articles for the second Delphi round. Survey response rates among SIG members were 29/75 for the first round and 24/75 for the second round. The advisory board added additional articles in the final review process in view of the overall project goal. A total of 60 articles were included in the final library, and articles were divided into seven sections and stratified by rating scores. A process for ongoing revisions of the library was determined. The library will be published on the Child Neurology Society website and made publicly accessible. Conclusions The CP SIGnature Library offers learners an unprecedented resource that provides equitable access to latest consensus guidelines, existing seminal datasets, up‐to‐date review articles, and other patient care tools. A distinctive feature of the library is its intentional large scope and depth, presented in a stratified fashion relative to the consensus‐determined importance of each article. Learners can efficiently navigate the library based on individual interests and goals, and the library can be used as core curriculum for CP education.